A Müncheni Südost-Institut tevékenysége és tudománypolitikai helyzete a 30-as évek közepétől a II. világháborús összeomlásig - Orosz, László (Közép-Európai Közlemények, 2015)
This work contains the second half of our examination of the endeavors of the most important institute specializing in research related to the so-called „Südostraum” region, the Munich-based Südost-Institut. Our earlier work concerned the formation of the institute and its early years (as well as how politics overshadowed academic / research pursuits during that period), and we observed a definitive break that marked a fundamental change in the direction of the endeavors of the institute. The line of demarcation was clearly the arrival of Fritz Valjavec (in October 1935) to the institute, who quickly would become its definitive personality. And as a result of his actions, the institute’s research priorities, publication structure and international networking (mainly in the direction of the Danube region) all fundamentally changed. This study takes a look at this new era of the institute, at the bridge that connected the beginning of the decade, when the institute undertook politically-driven work, to the end of the decade, by which time it had been transformed into an internationally respected academic / research institute specializing in the southeastern region. Despite the strengthening of its academic profile, we do not wish to claim, however, that political considerations played no role in the endeavors of the Südost-Institut up to its collapse near the end of WWII. That is the reason why we document not only examples of the process by which the institute changed its academic profile (via publication series, journals, library and media archives and university relation-ships), but also the extent to which political will nonetheless proved supreme in the functioning of the institute. We also take a brief look at the institute’s post-WWII existence.